Hands-on data warehousing with Azure Data Factory : ETL techniques to load and transform data from various sources, both on-premises and on cloud /: ETL techniques to load and transform data from various sources, both on-premises and on cloud. (2018) - Coté, Christian; Gutzait, Michelle; Ciaburro, Giuseppe
No abstract available